2019
DOI: 10.2134/jeq2019.02.0079
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Assessment of Ferrate Treatment of Metals in Acid Mine Drainage

Abstract: We report a preliminary assessment of ferrate [Fe(VI)] for the treatment of acid mine drainage (AMD), focused on precipitation of metals (i.e., iron [Fe] and manganese [Mn]) and subsequent removal. Two dosing approaches were studied to simulate the two commercially viable forms of Fe(VI) production: Fe(VI) only, and Fe(VI) with sodium hydroxide (NaOH). Subsequent metal speciation was assessed via filter fractionation. When only Fe(VI) was added, the pH remained <3.6, and the precipitation of Mn and Fe was <30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…These iron species are commonly called ferrates, and their potentials in energy materials, sustainable organic synthesis, and contaminant treatment processes have been shown. In the last two decades, many reviews regarding the synthesis and properties of Fe VI O 4 2– have been published. Fe VI O 4 2– possesses multimodal properties to induce simultaneous coagulation, disinfection, and oxidation in water treatment. , Fe VI O 4 2– can be reduced to iron­(III) oxides/hydroxides, which have been exploited as coagulants for the removal of phosphate, metals (e.g., copper and cadmium), metalloids (e.g., arsenic), and radionuclides (e.g., thallium). The generated core–shell structures of γ-Fe 2 O 3 and γ-FeOOH from Fe VI O 4 2– , identified by the unique combination of in-field low-temperature Mössbauer spectroscopy, X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS), were shown to capture metals directly from water.…”
Section: Introductionmentioning
confidence: 99%
“…These iron species are commonly called ferrates, and their potentials in energy materials, sustainable organic synthesis, and contaminant treatment processes have been shown. In the last two decades, many reviews regarding the synthesis and properties of Fe VI O 4 2– have been published. Fe VI O 4 2– possesses multimodal properties to induce simultaneous coagulation, disinfection, and oxidation in water treatment. , Fe VI O 4 2– can be reduced to iron­(III) oxides/hydroxides, which have been exploited as coagulants for the removal of phosphate, metals (e.g., copper and cadmium), metalloids (e.g., arsenic), and radionuclides (e.g., thallium). The generated core–shell structures of γ-Fe 2 O 3 and γ-FeOOH from Fe VI O 4 2– , identified by the unique combination of in-field low-temperature Mössbauer spectroscopy, X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS), were shown to capture metals directly from water.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there has not been a direct examination of the effectiveness of FeO 4 2− ions for the treatment of AMD. Most prior and preliminary works have focused on ferrate applications in wastewater [18][19][20][21], drinking water [4,22,23], oxidation of mine tailing and preventing acid drainage from uranium mill tailings [24], preliminary studies of ferrate treatment of metals in AMD [25], and TOC removal of surface water using ferrate (VI) [26]. However, this study aimed at conducting a preliminary treatment of synthetic AMD, using ferrate (VI) salt prepared through a wet oxidation method, assessment of metal concentrations in real AMD samples and their removal using sodium ferrate (VI) (Na 2 FeO 4 ) without using energy in a single mixing and dosing unit.…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary study was conducted using ferrate [Fe(VI)] for AMD treatment using two commercial forms of Fe(VI) only and Fe(VI) with NaOH, focusing on Fe and Mn precipitation and As removal (Goodwill, LaBar, Slovikosky, & Strosnider, 2019). The investigators found ferrate to be a viable option for AMD treatment and recommended additional studies to better develop this approach.…”
Section: Mine Drainage Remediation Technologymentioning
confidence: 99%